CRITICAL SUCCESS FACTORS FOR TOTAL QUALITY MANAGEMENT IMPLEMENTATION IN JORDANIAN HEALTHCARE SECTOR - Salaheldin, Salaheldin Ismail; Fathi, Samia; Shawaheen, Mohammad S. (European Scientific Journal, ESJ, 2015)
The purpose of this study is to investigate the role of creativity and innovation on the critical success factors of total quality management TQM implementation in the Jordanian healthcare sector. A survey conducted through distributing 377 questionnaires to healthcare managers working at six different Jordanian hospitals. 292 questionnaires were returned and the response rate was 77.4%. One way- ANOVA test was used to examine the difference in the patterns of creativity and innovation among healthcare managers with respect to the critical success factors of TQM implementation, and multiple regression analysis was conducted to test the impact of independent variable on dependent variables. The results found that there is a statistically significant difference between the different patterns of creativity and innovation concerning the critical success factors of TQM implementation. Additionally the study concluded for a positive and significant effect for the patterns of creativity and innovation on the critical success factors of TQM implementation (β=1.54, t=5.09, p=0.000).